PENGARUH STRES KERJA DAN KONFLIK KERJA TERHADAP KINERJA KARYAWAN - Julvia, Cristine (Ilmiah Manajemen Bisnis, 2016)
ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ  ABSTRACTJob stress and work conflicts can affect the performance of employees, aim of this study to determinethe effect of job stress and work conflict on employee performance, for it carried suervei andquestionnaires to obtain data. Data that has been tested and declared valid and reliable descriptiveand quantitative analysis and multiple linear regression analysis with the help of (SPSS version20 oÃ¢â¬â¢clock). from the analysis of the effect of work stress with the performance of the employee, itis known that the result was a significant negative effect, which means that when the stress level isreduced then the performance will increase, while the results of analysis of the effect of work conflictwith the employeeÃ¢â¬â¢s performance was found to significantly and positively.Keywords: employee performance, job stress, work conflictÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ  ABSTRAKStress kerja dan konflik kerja dapat berpengaruh terhadap kinerja karyawan, Tujuan penelitian iniuntuk mengetahui pengaruh stress kerja dan konflik kerja terhadap kinerja karyawan, Untuk itudilakukan suervei dan penyebaran kuesioner untuk memperoleh data. Data yang telah dilakukanuji dan dinyatakan valid dan reliabel dianalisis deskriptif dan kuantitatif dan analisis regresi linerberganda dengan bantuan (Program SPSS versi 20.00). dari hasil analisis mengenai pengaruh stresskerja dengan kinerja karyawan, diketahui bahwa hasilnya adalah signifikan berpengaruh negatif,yang artinya bila tingkat stres dikurangi maka kinerja akan meningkat, sedangkan pada hasil analisispengaruh konflik kerja dengan kinerja karyawan didapati signifikan berpengaruh positif.Kata kunci: kinerja karyawan, stress kerja, konflik kerja